2017
DOI: 10.1371/journal.pone.0169652
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Antidepressant Medication before and after the Onset of Unemployment by Subsequent Employment Experience

Abstract: BackgroundThe unemployed more often suffer from depression than the employed. We examined whether mental health deterioration occurs already before unemployment implicating health selection, or whether it mostly occurs after becoming exposed to the experience rendering causal explanations more likely.MethodsWe used nationally representative Finnish register data to examine changes in depressive morbidity as measured by antidepressant medication in 1995–2009 over four years before and since a new onset of unemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
2
4
0
1
Order By: Relevance
“…Considering previous studies, the findings herein contrast with other research that have found that retirement (compared to remain working) was associated with a higher risk of depression, so that the timing ( Buxton, Singleton, & Melzer, 2005 ), the duration ( Olesen, Rod, Madsen, Bonde, & Rugulies, 2015 ) and the wilfulness ( Mosca & Barrett, 2016 ) of retirement were key features that influenced the mental health of older adults. Contrarily, our results are similar to those presented in other investigations where a protective association between retirement (versus working) and depression has been reported ( Mandal and Roe, 2008 , Westerlund et al, 2010 ) or where at least there was not an increase of depressive symptoms given by partial ( Szinovacz & Davey, 2004 ) and statutory retirement ( Leinonen, Mäki, & Martikainen, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Considering previous studies, the findings herein contrast with other research that have found that retirement (compared to remain working) was associated with a higher risk of depression, so that the timing ( Buxton, Singleton, & Melzer, 2005 ), the duration ( Olesen, Rod, Madsen, Bonde, & Rugulies, 2015 ) and the wilfulness ( Mosca & Barrett, 2016 ) of retirement were key features that influenced the mental health of older adults. Contrarily, our results are similar to those presented in other investigations where a protective association between retirement (versus working) and depression has been reported ( Mandal and Roe, 2008 , Westerlund et al, 2010 ) or where at least there was not an increase of depressive symptoms given by partial ( Szinovacz & Davey, 2004 ) and statutory retirement ( Leinonen, Mäki, & Martikainen, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, the present study adheres to the growing body of literature that suggests retirement has a protective effect on mental health when it is voluntary or includes a pension, features that are not always specified, making it difficult to synthesize the evidence. Theoretically, some authors have proposed that retirement may increase depression, especially when: 1) it occurs sooner than expected, 2) it is perceived as forced, and 3) it is abrupt rather than gradual ( Leinonen et al, 2017 ). Based on this theory, a “good retirement” (right timing, gradual, voluntary, and well paid) should not be related to depression.…”
Section: Discussionmentioning
confidence: 99%
“…We found that unemployment was associated with decreasing use of antidepressants similar to other studies, which have found that unemployment status correlates with decreasing antidepressant use [38]. This effect is thought to be driven by health selection, whereby mental health status deteriorates before unemployment, and then improves during unemployment [39,40], perhaps due to relief of work related stressors. Living alone had stronger associations with antidepressants in another study (OR 1.81; 95%CI 1.46-2.23) [25] than in the current study (OR ranged from 1.10 to 1.28 for 'decreasing', 'increasing' and 'most of the time' groups), which may be explained by the differences in sample .…”
Section: Comparison With Existing Literaturesupporting
confidence: 83%
“…These studies, however, did neither examine long-term trends in antidepressant use nor distinctive antidepressant classes, which may have masked some associations. Furthermore, a recent study concluded that the differences by employment status may arise from health selection (Leinonen et al 2017), which means that those with mental health problems are more likely to become selected into unemployment than vice versa.…”
Section: Discussionmentioning
confidence: 99%